Monoclonal gammopathy of undeterminated significance and endoneurial IgG deposition: A case report. Issue 36 (September 2016) - Mathis, Stéphane; Franques, Jérôme; Richard, Laurence; Vallat, Jean-Michel
Abstract: Background: Monoclonal gammopathy of undeterminated significance is the most common form of plasma cell dyscrasia, usually considered as benign. In rare cases it may have a malignant course, sometimes limited to an organ such as peripheral nerves. Methods: We describe clinical, electrophysiological and pathological findings in a patient presenting a immunoglobulin G (IgG) paraproteinemic polyneuropathy clinically mimicking a chronic inflammatory demyelinating polyneuropathy. Results: Immuno-electron microscopy (immune-EM) demonstrated that the widenings of the myelin lamellae resulted from the infiltration of IgG between a significant number of myelin lamellae (with absence of inflammatory cells in the epineurium, endoneurium, and perineurium, and the lack signs of vasculitis). This patient was finally treated successfully with lenalidomide then mycophenolate mofetil. Conclusions: In polyneuropathies associated to a monoclonal gammopathy, a nerve biopsy may clinch the diagnosis. Immuno-EM may be required to determine the role of the pathological immunoglobulin in the destruction of the peripheral nerve parenchyma. Diagnosis of such a direct involvement of peripheral nerve can endorse more aggressive treatment of real efficiency.